Correlates of physical activity in children and adolescents with intellectual disabilities: a systematic review. Issue 5 (16th February 2021) - Sutherland, L.; McGarty, A. M.; Melville, C. A.; Hughes‐McCormack, L. A.
Abstract: Background: Children and adolescents with intellectual disabilities (ID) participate in low levels of physical activity. To inform the development of interventions, we need to better understand factors associated with physical activity. The aim of this study was therefore to systematically review correlates of physical activity in children and adolescents with ID. Methods: The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Ovid MEDLINE, Ovid Embase, Web of Science, ERIC, CINAHL and PsycINFO were searched between 1 January 1990 and 29 February 2020 to identify English‐language studies, which examined correlates of free‐living physical activity in children and adolescents (0–19 years) with ID. Study quality was assessed. Correlates were analysed using a narrative synthesis and classified using the socioecological model as intrapersonal, interpersonal, organisational or environmental. Results: Fifteen studies published between 2010 and 2019 met the inclusion criteria and were included in the review. Forty‐eight individual correlates were identified. Studies were predominantly focused on intrapersonal‐level correlates. Of those correlates investigated in more than one study ( n  = 6), having better motor development was positively associated with physical activity. Inconsistent results were found for age and cardiorespiratory fitness. Sex, percentage body fat and body mass index were not correlated. No interpersonal‐level, organisational‐level or environmental‐level correlates were included in more than one study. Conclusions: To date, we have limited and inconclusive evidence about correlates of physical activity in children and adolescents with ID. Only when future studies unravel correlates and determinants, across all domains of the socioecological model, will the potential opportunities to improve health by increasing physical activity levels be achievable.